Orbitally-driven evolution of Lake Turkana (Turkana Depression, Kenya, EARS) between 1.95 and 1.72 Ma: A sequence stratigraphy perspective. (January 2017) - Nutz, Alexis; Schuster, Mathieu; Boës, Xavier; Rubino, Jean-Loup
Abstract: Lakes act as major archives for continental paleoenvironments, particularly when the evolution of lake levels over time serves as a guide for understanding regional paleohydrology and paleoclimate. In this paper, two sections from the Nachukui Formation (Turkana Depression, East African Rift System) provide a complete record of lake level variability and then paleohydrology for Lake Turkana between 1.95 and 1.72 Ma. This period corresponds to a key time during which important human evolutionary and technological innovations have occurred in East Africa and in the Turkana area. Based on sedimentary facies and sequence analyses on coastal deposits, one long-term regressive-transgressive cycle is identified between 1.95 and 1.72 Ma. Superimposed on this trend, five higher-frequency cycles of lake level change are identified between 1.87 and 1.76 Ma. Origins of these periodicities are attributed to orbital forcings. The extents of bathymetry change and shoreline migration during these periods are explored, suggesting that the period between 1.87 and 1.76 Ma was relatively dry and that climate experienced a relatively low variability. This finding differs strongly from most of the previous paleoenvironmental investigations in the region that argue high climate variability during a relatively wet period. This work emphasizes the importance of using sequence stratigraphy for analyzing lacustrine deposits. Highlights: Coastal deposits 1.95 to 1.72 Ma old are investigated in the Turkana Depression. Wave-dominated coastal sedimentary features record the evolution of paleo-Lake Turkana. Two orbitally-driven orders of regressive-transgressive cycles are revealed. Low climate variability characterize the period between 1.95 and 1.72 Ma.